Impact on water distribution system biofilm densities from reverse osmosis membrane treatment of supply water. Issue 4 (1st July 2007) - Meckes, Mark C; Haught, Roy C; Kelty, Keith; Blannon, Janet C; Cmehil, David
Abstract : The quality of potable water is such that the concentration of nutrients available for growth of microorganisms within distribution systems is limited. In such systems carbon is often the growth limiting nutrient. Research conducted in the Netherlands has indicated that low levels (<10  μ g/L) of available organic carbon in water is sufficient to maintain an actively growing population of heterotrophic, or organic carbon utilizing, bacteria in aquatic systems. However, the ability of commercially available and cost effective technologies to achieve such low concentrations of assimilable organic carbon in full-scale water systems is doubtful. Reverse osmosis (RO) systems have been used for many years to effectively remove contaminants from source waters. We challenged a water distribution system simulator (DSS) with water from a municipal system and water that was treated using an RO system under two concentrations of residual free chlorine to evaluate the effect of this disinfectant on biofilms in contact with low nutrient water. Our results showed that biofilm densities in the DSS carrying low nutrient RO treated water were lower than biofilm densities taken from the DSS when it carried water directly obtained from a municipal system. Key words: water distribution systems, reverse osmosis, biofilms, heterotrophic plate count, HPC, chlorine, assimilable organic carbon.